New treatment approaches in relapsing/refractory primary central nervous system lymphomas - Guven, Serkan; Yavuz, Boran; Karatas, Aylin Fatma; Erdogan Yucel, Elcin; Ozsan, Guner Hayri; Demirkan, Fatih; Ozer, Erdener; Alacacioglu, Inci (Annals of Medical Research, 2022)
Aim: Primary central nervous system lymphoma (PCNSL) is a rare disease that affects the brain, leptomeninges, spinal cord, cerebrospinal fluid, or vitreoretinal compartment without evidence of systemic disease. Although some treatment success is achieved with high dose methotrexate-based regimens, the prognosis is still poor. In this respect, new therapeutic approaches are required.Materials and Methods: The clinical data of 6 patients diagnosed with primary central nervous system lymphoma in a hematology center of a university hospital were analyzed for 3 years. Ibrutinib monotherapy was applied to these 6 refractory patients as the last-stage treatment. The results were evaluated.Results: Six patients (5 women, 1 man) with relapsed and refractory PCNSL received ibrutinib as monotherapy. As initial treatment, 3 patients received high-dose methotrexate + rituximab, 1 patient received MATRix (Rituximab, Methotrexate, Cytarabine, Thiotepa), 1 patient received high-dose methotrexate. Only one patient received radiotherapy (RT), following the initial treatment. Two patients were consolidated with autologous transplantation and one patient with RT. All patients received treatment at a dose of 560 mg. No serious side effects have been detected. Three patients who received ibrutinib monotherapy for the shortest 1 month and the longest 24 months died. The patient, who has been on ibrutinib monotherapy for 11 months, is being followed up stably.Conclusions: We have demonstrated the therapeutic benefit of ibrutinib as monotherapy in our refractory patients. However, we believe that using ibrutinib as part of combination therapy at the initial stage of the disease would yield better results.
Keywords: Primary CNS lymphoma; Ibrutinib; Rituximab; Radiotherapy